Pengaruh Motivasi, Sanksi Pajak dan Ajaran Tri-Nga terhadap Niat Melakukan Kecurangan oleh Calon Wajib Pajak (Studi Kasus pada Mahasiswa Universitas Sarjanawiyata Tamansiswa) - Prastyatini, Sri Lestari Yuli; Pratama, Alfian Aji (Ekonomis: Journal of Economics and Business, 2024)
This study aims to prove the effect of motivations, tax sanctions, and tamansiswa teachings “Tri-Nga” on student intentions to commit fraud by prospective taxpayers. This research is quantitative and the type of primary data. This study used 100 respondents, namely accounting students at the tamansiswa bachelor of laws university. This study uses multiple linear regression analysis, where the results of the study show evidence that there is a positive influence on lifestyle on motivations, tax sanctions, and tamansiswa teachings “Tri-Nga” have effect on student’s intentions to commit fraud by prospective taxpayers.